1994
DOI: 10.1152/jappl.1994.77.2.548
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia stimulates nitric oxide formation: electron paramagnetic resonance detection of .NO-heme in blood

Abstract: Previous experiments from our laboratory have demonstrated that severe hyperthermia results in a selective loss of splanchnic vasoconstriction. Using electron paramagnetic resonance spectroscopy to scan whole blood samples collected in vivo from the portal vein and femoral artery of conscious unrestrained rats, we observed an increase in the concentration of spectroscopy-detectable species in portal venous blood of all heat-stressed animals. These spectra consisted of at least three distinct species: one with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 25 publications
3
103
0
1
Order By: Relevance
“…The increased levels of NO immediately subsequent to the insult would cause the observed increases in CBF, CBV and the absent CBVR (this response would already be saturated with NO). Hypothermia is cerebroprotective in our piglet model ; intriguingly hyperthermia has recently been shown to stimulate NO production in i o (Hall et al 1994). Also, the close links recently shown between nitric oxide, mitochondrial damage and apoptosis are also consistent with our model (Shimaoka et al 1995 ;Liu et al 1996).…”
Section: (B) Neonatal Hypoxia-ischaemiasupporting
confidence: 85%
“…The increased levels of NO immediately subsequent to the insult would cause the observed increases in CBF, CBV and the absent CBVR (this response would already be saturated with NO). Hypothermia is cerebroprotective in our piglet model ; intriguingly hyperthermia has recently been shown to stimulate NO production in i o (Hall et al 1994). Also, the close links recently shown between nitric oxide, mitochondrial damage and apoptosis are also consistent with our model (Shimaoka et al 1995 ;Liu et al 1996).…”
Section: (B) Neonatal Hypoxia-ischaemiasupporting
confidence: 85%
“…For instance, lipopolysaccharides, classic inducers of NO synthesis [8], also activate HSP70 synthesis [9]. On the other hand, HS, which is a conventional factor inducing HSP synthesis [1,2,10], is attended by an increase in nitrosyl heme content in blood [11]. Our own experiments have demonstrated that adaptation of the organism to stress both activates HSP70 synthesis [7] and potentiates NO generation in the same organs [12].…”
Section: Introductionmentioning
confidence: 99%
“…In intact rats, it is demonstrated that high hyperthermic conditions increased formation of ROS in the portal circulation (Hall et al, 1994;Lin et al, 2006). In broiler chickens, high ambient temperature increased plasma MDA which indicated an oxidant/antioxidant equilibrium disturbance leading to oxidative stress (Lin et al, Abbreviations: BHT, butylated hydroxytoluene; Zn, zinc; PHE300, purslane hydroextract 300 mg kg −1 of diet; PHE600, purslane hydroextract 600 mg kg −1 of diet; ZPHE300, zinc 100 mg kg −1 diet + purslane hydroextract 300 mg kg −1 of diet; ZPHE600, zinc 100 mg kg −1 diet + purslane hydroextract 600 mg kg −1 of diet; MDA, malondialdehyde; TAC, total antioxidant capacity; CAT, catalase; SRBC, sheep red blood cells; HA, hemagglutination assay; SEM, standard error of means; values are means ± SEM.…”
Section: Discussionmentioning
confidence: 99%